First isolation of Salmonella enterica serovar Napoli from wild birds in Italy - Laura Mancini; Stefania Marcheggiani; Annamaria D'Angelo; Camilla Puccinelli; Filippo Chiudioni; Flavia Rossi; Elisabetta Delibato; Dario De Medici; Anna Maria Dionisi; Slawomir Owczarek; Ida Luzzi (Istituto Superiore di Sanità, 2014)
Salmonella enterica serovar Napoli (S. Napoli) is an emerging serovar in Italy. It accounts for 2-4% of all serovars isolated from human infections. The zoonotic origin of this serovar is still unknown and this makes difficult to apply any control intervention. We report here the isolation of S. Napoli from a river nightingale (Cettia cetti, Temminck 1820) which represents the first description of this serovar from wild birds. This finding adds knowledge to the ecology of S. Napoli and addresses further studies aimed to assess the epidemiologic link between S. Napoli isolated from wild birds, food, environmental sources and human infections.